Factor Xa Inhibitors for Patients after Mechanical Heart Valve Replacement? - Gerfer, Stephen; Grandoch, Maria; Wahlers, Thorsten C.W.; Kuhn, Elmar W. (The Thoracic and Cardiovascular Surgeon, 2021)
Patients with a mechanical heart valve need a lifelong anticoagulation due to the increased risk of valve thrombosis and thrombo-embolism. Currently, vitamin K antagonists (VKA) are the only approved class of oral anticoagulants, but relevant interactions and side effects lead to a large number of patients not achieving the optimal therapeutic target international normalized ration (INR). Therefore, steady measurements of the INR are imperative to ensure potent anticoagulation within a distinctive range. Direct oral anticoagulants (DOACs) with newer agents could serve as a possible alternative to VKAs in this patient cohort. DOACs are approved for several indications, e.g., atrial fibrillation (AF). They only have a minor interaction potential, which is why monitoring is not needed. Thereby, DOACs improve the livability of patients in need of chronical anticoagulation compared with VKAs. In contrast to dual platelet inhibition using aspirin in combination with an ADP receptor antagonist and the direct thrombin inhibitor dabigatran, the oral factor Xa inhibitors apixaban and rivaroxaban show promising results according to current evidence. In small-scale studies, factor Xa inhibitors were able to prevent thrombosis and thrombo-embolic events in patients with mechanical heart valves. Finally, DOACs seem to represent a feasible treatment option in patients with mechanical heart valves, but further studies are needed to evaluate clinical safety. In addition to the ongoing PROACT Xa trial with apixaban in patients after aortic On-X valve implantation, studies in an all-comer collective with rivaroxaban could be promising.
Keywords: direct oral anticoagulation; dabigatran; rivaroxaban; Edoxaban; apixaban; mechanical heart valve; mechanical mitral valve; mechanical aortic valve